The Correlation among Self-Efficacy, Cognitive Strategy, and Students’ Speaking Achievement of Eleventh Graders at SMK Kesehatan Kader Bangsa Palembang - Anggi Anggraini (Program Pendidikan Bahasa Inggris Universitas Tridinanti, 2024)
The objective of this study was to find out whether or not there was a significant correlation among self-efficacy, cognitive strategy, and student speaking achievement of students at SMK Kesehatan Kader Bangsa Palembang. 65 eleventh-grade students were involved as the sample, selected using purposive sampling techniques. The correlational method was applied as the research design. Questionnaires and test were used as data collection instruments. To analyze the data, the writer used a correlational analysis to examine the correlation among the variables. The result of the correlational analysis indicated that there was no correlation between the students’ self-efficacy and speaking achievement. The result of Spearman-Brown showed that the value of r-obtained was -0.096, with a significance value was 0.448 and it was lower than 0.5. The results of correlational analysis between the students' self-efficacy and speaking achievement also showed that there was no correlation between students’ cognitive strategy and their speaking achievement since the value of r obtained was -0.030. In conclusion, these results are explained by the fact that there was no significant relationship between the students’ self-efficacy, cognitive strategies, and students' speaking achievement.